Edukasi Urgensi Vaksinasi Covid-19 Bagi Masyarakat Desa Buntu, Kecamatan Kroya, Kabupaten Cilacap - Nugroho, Adi; Prima, Ellen (Solidaritas: Jurnal Pengabdian, 2022)
The low enthusiasm and awareness of Buntu Village, Kroya District, Cilacap Regency towards participation in the Covid-19 vaccine program have encouraged the Family Empowerment and Welfare Team (PKK) to educate the public about the importance and benefits of the Covid-19 vaccine. The method of community service activities is carried out through 3 sessions, specifically the preparation, implementation and evaluation stages. The preparatory stage is coordinated with PKK administrators and the health team from the local health centre. The implementation stage provides material regarding the understanding and impact of the Covid-19 virus, the importance of vaccines, and the safety and halalness of vaccines. It ends with discussions and questions and answers. The PKK Team carried out the evaluation stage, asking participants questions related to educational materials to measure the level of participants’ understanding of educational materials. At the end of the session, the participants were also asked to share their vaccination program perceptions after receiving the educational materials. Based on the answers, it was found that the participants have changed their perception of the Covid-19 vaccination from being apathetic and refusing to be supportive and ready to participate in vaccinations.